Comparison of dry matter losses and aflatoxin B1 contamination of paddy and brown rice stored naturally or after inoculation with Aspergillus flavus at different environmental conditions - Martin, Sara; Medina-Vayá, Ángel; Magan, Naresh (Journal of Stored Products Research, 2017)
The objective of this study was to compare the effect of different storage moisture conditions (0.70, 0.85, 0.90 and 0.95 water activity, aw) and temperatures (20, 25, 30 °C) on (a) respiration rates (R) and dry matter loss (DML) of paddy and brown rice and (b) quantify aflatoxin B1 (AFB1) production by isolates of Aspergillus flavus from the rice samples and (c) inoculation of both rice types with A. flavus under these storage conditions on R, DML and AFB1 contamination. There was an increase in temporal CO2 production with wetter and warmer conditions in naturally contaminated rice. Higher R and consequently, % DML, were generally found in the brown rice (21%) while in paddy rice this was only up to 3.5% DML. From both rice types, 15 (83.3%) of 18 A. flavus isolates produced detectable levels of AFB1 in a range 2.5–1979.6 μg/kg. There was an increase in DML in both rice types inoculated with A. flavus as temperature and aw were increased. Interestingly very little AFB1 was detected in paddy rice, but significant contamination occurred in the brown rice. The %DML in the control and A. flavus inoculated rice increased with temperature and aw at both 25 and 30 °C from 1-2% to 15–20% DML at 30 °C and 0.95 aw. All the inoculated rice samples had AFB1 levels above the EU legislative limits for contamination in other temperate cereals and products derived from cereals (=2 μg/kg). Even samples with % DML as low as 0.2% had AFB1 contamination levels twice the limits for other cereals. These results suggest that the mycotoxin contamination risk in staple commodities like rice, is influenced by whether the rice is processed or not, and that measurement of R rates can be used to predict the relative risk of AFB1 contamination in such staple commodities.